Implementasi Program Sosial Bank Indonesia (PSBI) dalam Mempertahankan Citra Perusahaan Bank Indonesia Provinsi Jawa Barat: Studi Kasus mengenai Program Sosial Bank Indonesia Provinsi Jawa Barat - Fariq Hafizhan Kurniawan (UNISBA Press, 2023)
Abstract. This research exposes the context of research on the importance ofining the corporate image, for the Bank Indonesia Province of West Java and how the Social Program of the Bank of Indonesia (PSBI) can help in achieving those goals. The research also highlighted the implementation of the Social Bank Indonesia Program (PSBI) in the Indonesian Bank Office of the West Java Province as a case study. The study aims to analyze the implementation of the Social Program of the Bank of Indonesia (PSBI) in the Indonesian Bank’s office in the West Java Province inining the company’s image. This research uses a qualitative approach with case study methods. The research uses data collection techniques through interviews, observations, documentation, and literature studies. The results of the discussion on this study are criteria in the Indonesian Bank Office of the Province of West Java, the determination of recipients of social assistance (PSBI) is based on economic needs and social vulnerabilities. These criteria include non-governmental ownership, entrepreneurship or management, and priority scholarships for prehistoric families. The implementation of the Social Program of the Bank of Indonesia (PSBI) at the Indonesian Bank’s office in the West Java Province is an important effort to maintain the company’s image. PSBI can gain a reputation as a caring and socially responsible institution by participating in programs that benefit the community. By applying the method by monitoring, evaluation periodically, so that its effectiveness has a good impact. The aim of establishing the Social Program of the Bank of Indonesia is to maintain economic stability or rupiah value, as well as maintain the positive reputation of the company as a central bank Abstrak. Penelitian ini memaparkan konteks penelitian mengenai pentingnya mempertahankan citra perusahaan, bagi Bank Indonesia Provinsi Jawa Barat dan bagaimana Program Sosial Bank Indonesia (PSBI) dapat membantu dalam mencapai tujuan tersebut. Penelitian in juga menyoroti implementasi Program Sosial Bank Indonesia (PSBI) di Kantor Bank Indonesia Provinsi Jawa Barat sebagai studi kasus. Penelitian ini bertujuan untuk menganalisis implementasi Program Sosial Bank Indonesia (PSBI) di Kantor Bank Indonesia Provinsi Jawa Barat dalam mempertahankan citra perusahaan. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kasus. Penelitian ini menggunakan teknik pengumpulan data melalui wawancara, observasi, dokumentasi, dan studi literatur. Hasil Pembahasan pada penelitian ini adalah kriteria di Kantor Bank Indonesia Provinsi Jawa Barat, penentuan penerima bantuan sosial (PSBI) didasarkan pada kebutuhan ekonomi dan kerentanan sosial. Kriteria tersebut mencakup kepemilikan di luar pemerintahan, kepengerusahaan atau pengelolaan, dan prioritas beasiswa untuk keluarga prasejarah. Implementasi Program Sosial Bank Indonesia (PSBI) di Kantor Bank Indonesia Provinsi Jawa Barat merupakan upaya penting untuk mempertahankan citra perusahaan. PSBI dapat memperoleh reputasi sebagai lembaga yang peduli dan bertanggung jawab sosial dengan berpartisipasi dalam program yang bermanfaat bagi masyarakat. Dengan menerapkan metode dengan memonitoring, evaluasi secara berkala, sehingga efektivitasnya berdampak baik. Tujuan membentuk Program Sosial Bank Indonesia adalah salah satunya menjaga stabilitas ekonomi atau nilai rupiah, serta mempertahankan reputasi positif perusahaan sebagai bank sentral